2004
DOI: 10.2135/cropsci2004.7480
|View full text |Cite
|
Sign up to set email alerts
|

Chicory Root Yield and Carbohydrate Composition is Influenced by Cultivar Selection, Planting, and Harvest Date

Abstract: Chicory (Cichorium intybus L.) is not extensively grown in the USA for fructan production, and there is limited information available on the effect of cultural practices on root yield. Three field experiments were conducted from 1995 through 2002 to determine the influence of planting and harvest date and cultivar on yield and carbohydrate composition of chicory roots. Different chicory cultivars were planted from the first of April through mid‐May and were monitored for plant stand, leaf area, and bolting dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 10 publications
3
24
0
Order By: Relevance
“…ha -1 DM reported from New Zealand [19]. Wilson et al [29], reported root yields alone for chicory of 3600 to 5500 kg ha -1 DM in Nebraska. Our chicory yields were also well below those from southern Alberta where chicory (6400 kgha -1 DM) outyielded corn silage crops (Bandara M, unpublished data).…”
Section: Forage Yieldmentioning
confidence: 99%
“…ha -1 DM reported from New Zealand [19]. Wilson et al [29], reported root yields alone for chicory of 3600 to 5500 kg ha -1 DM in Nebraska. Our chicory yields were also well below those from southern Alberta where chicory (6400 kgha -1 DM) outyielded corn silage crops (Bandara M, unpublished data).…”
Section: Forage Yieldmentioning
confidence: 99%
“…Before the hydroponic cultivation of chicory, the total sugar concentration in the roots was reported to be much higher (15.3-20.1 % of fresh weight). 34 For the development of the pre-treatment protocol, several conditions were studied. In order to follow the extraction progress, the oligomeric carbohydrates were determined.…”
Section: Pre-treatment Of Chicory Rootsmentioning
confidence: 99%
“…Schittenhelm (2001) reported that root chicory is a potential alternative sugar crop which accumulates a high amount of linear fructose polymers (fructan) in its roots. Wilson et al (2004) reported that glucose, fructose, sucrose, and fructans were as a percentage of total sugar content. Andrea et al (2005) reported that fructans were further grouped into three categories: DP 3 to 10 fructans (short chain-length fructans), DP 11 to 20 fructans (medium chain-length fructans) and DP > 20 fructans (long chain-length fructans).…”
Section: Introductionmentioning
confidence: 99%